Equal or equitable pay? Individual differences in pay fairness perceptions - Kim, Tae‐Yeol; Wang, Jie; Chen, Tingting; Zhu, Yue; Sun, Rui (Human Resource Management, 2018)
This study examined how social comparison (i.e., comparing one's pay to similar others' pay) and deserved comparison (i.e., comparing one's pay to one's deserved pay) affect pay fairness perceptions, and the individual differences in the comparison processes. Results based on a field study with a sample of 167 employees showed pay fairness was low when employees received lower pay than a similar other (or what they deserved), increased as their pay exceeded that of a similar other (or deserved pay) to some extent, and then decreased when overpayment was considerable. Second, pay fairness increased as one's actual and similar others' pay levels both increased while pay fairness remained the same as one's actual and the deserved pay levels both increased. In addition, the “threshold” that people start to perceive overpayment as less fair occurred more quickly for those with higher preference for consistency in social comparison and for those with higher preference for the merit principle in deserved comparison. We also conducted experiments, and the results generally replicated the findings in the field study. These findings offer theoretical implications regarding organizational justice, as well as practical implications for designing and executing a compensation system.